Annotated checklist of cladocerans from La Venturosa lagoon with first report of Leydigiopsis curvirostris for Colombia - Elmoor-Loureiro, Lourdes M.A. (2025)
Thirty-nine cladoceran species were recorded from La Venturosa lagoon in the Orinoquia region of Colombia. Of these, 17 species represent new records for the Meta Department, and Leydigiopsis curvirostris Sars, 1901 is reported for the first time in Colombia. With these additions, the total number of cladoceran species known from Colombia and the Meta Department increases to 127 and 58, respectively. The cladoceran fauna of the surveyed area is composed mainly of widespread species commonly found in Neotropical regions, although local morphological information remains scarce in the regional literature. Here, we provide brief diagnostic descriptions of the most relevant species recorded in the Meta Department, together with illustrations of taxonomically significant appendages, morphological remarks, notes on intraspecific variability, and distributional data.